The physicochemical and nutritional properties of biscuits from low temperature dried breadfruit (Artocarpus altilis (Parkinson) Fosberg) flour - Levai, L.D.; Tang, E.N.; Monono, Y.E.; NDikum, S.B.; Eyenga, E.F.; Sumbele, S.A.; Ngane, B.K.; Schneider, J.; Birmingham, T.; NDindeng, S.A.; NGome, F.A. (Springer, 2024)
To reduce postmaturity losses and increase awareness of breadfruit (Artocarpus altilis) food value and versatility, we characterized the physicochemical, nutritional and sensory properties of sundried (96 h ± 28oC) and oven dried (72 h, 50oC) breadfruit flour and biscuits. Our findings revealed that breadfruit flour and biscuits are rich in essential minerals of public health concern, with iron being particularly high in the biscuits. Biscuits from sundried flour (BSDF) and oven-dried flour (BODF) could contribute respectively 10.89% and 10.83% of the daily Fe needs for adults and children above 4 years. The zinc content did not differ significantly between drying methods, but increased significantly to 4.88 and 4.93 mg/100 g in BSDF and BODF, respectively. The BSDF and BODF could, respectively, provide 13.05% and 18.15% of the daily energy requirement for an individual with a recommended daily intake of 2000 kcal. The lightness varied significantly with the drying method, and the oven dried flour (ODF) had the highest L* value. The gelatinization temperature (75.48 vs. 73.20oC) of ODF was significantly higher than that of sundried flour (SDF). The setback, breakdown, final, peak, and trough viscosities of the SDF were significantly lower than those of the ODF, suggesting that the SDF is suitable for infant and instant food formulations. Taste, aroma, crispiness, greasiness, and overall acceptability did not differ significantly (Prob>|t|=0.21), but granulometry and melting (Prob>|t|=0.03) differed significantly between BSDF and BODF. In conclusion, breadfruit can be successfully processed into acceptable cookies that provide essential nutrients to meet daily recommended intakes.